Analysis of Water Pollution due to Development Activities and Its Impact on the Citarum River in Indonesia - Ferdinand Ferdinand; Ariya Darma; Amanatullah Savitri (Fakultas Teknik Sipil dan Perencanaan, 2023)
Water pollution, especially in rivers like the Citarum River in Indonesia, is an urgent environmental issue. Factors such as inadequate industrial waste management, infrastructure development that disrupts water flow and increases soil erosion, intensive agriculture with excessive use of fertilizers and pesticides, tourism sector development without adequate waste management, improper disposal of domestic waste, and improper waste management all contribute to the degradation of water quality in the Citarum River. The impacts of water pollution are highly detrimental. The polluted river experiences a decline in water quality that can endanger the lives of humans, animals, and plants that depend on the river. Water pollution also has negative effects on river ecosystems, including disruptions to the food chain, loss of biodiversity, and habitat destruction.To address this problem, a sustainable development approach that considers environmental impacts is needed. This includes adopting environmentally friendly technologies, improving waste management, and planning development that focuses on the balance of river ecosystems. By implementing these measures, it is hoped that the Citarum River can be protected and ensure the sustainability of the water ecosystem for future generations.The importance of awareness of the impact of development on the environment also needs to be emphasized. The community needs to realize that their individual and collective actions can affect the quality of river water and its ecosystem. Collaboration between the government, industry, the community, and non-governmental organizations is also crucial. Cooperation in monitoring, law enforcement, and the implementation of policies that support clean and healthy water management needs to be enhanced.